Perspectives of a teaching tandem integrating the writing of textual genres in French and English at the primary level in Québec: - Thibeault, Joël; Forget, Marie-Hélène (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2024)
This article presents the results of an exploratory study conducted in an intensive English program in Québec. A French classroom teacher and an English as a second language teacher simultaneously cotaught two units on writing genres (recommendations and opinion letters) to grade-6 students. Using data from a series of individual semi-structured interviews conducted after each unit, we focus on the teachers’ points of view regarding the parameters of each integrated unit, the students’ experiences throughout the linguistic integration as well as the coteaching of languages in an integrated way.